Corporate responsibility and stakeholding - Crowther, David; Seifi, Shahla (Bingley, U.K. : Emerald, 2016)
Although much consideration has been given to the relationship between a corporation and its stakeholders, less attention has been given as to who those stakeholders might consist of. Nevertheless in this globalised world the effects of the actions of a corporation can been seen to extend far beyond the boundaries of the organisation and far beyond the countries in which that corporation is domiciled or operates. Indeed not only can a butterfly flapping its wings cause a hurricane in another part of the world but also a minor decision by a corporation can have a dramatic social, economic or geopolitical impact in other parts of the world. Thus the stakeholder community of a corporation must be considered as far greater than its voluntary stakeholders, far greater than its internal stakeholders and far greater than its supply chain and value chain. This has considerable implications for the corporation and its approach to both its operations and its sense of corporate responsibility. Too often this is not considered or even recognised so in this book we take the widest definition of stakeholders and consider aspect of the corporation's responsibility to this community.
Hyper-transparency: the stakeholders uprising / Amir Hossein Rahdari -- The role of shapeholders as a link between a firm and non-stakeholders: the pursuit of an economy for the common good based on stakeholder theory / Jose<U+0301> Luis Retolaza, Leire San-Jose, Ricardo Aguado -- Microfinance and women empowerment / M. Abu Naser, David Crowther -- Managing with depleted resources / Shahla Seifi, David Crowther -- Corporate stakeholding and globalism: a need for revision of the stakeholder concept using the resist-model against "business-as-usual" / Linne Marie Lauesen -- Influences on stakeholder engagement in sustainability accounting and reporting: a study of Australian local councils / Amanpreet Kaur, Sumit Lodhia -- Determinants of sustainability e-reporting in Portuguese municipalities: an institutional and legitimacy theoretical framework / Vero<U+0301>nica Paula Lima Ribeiro, So<U+0301>nia Maria Da Silva Monteiro, Ana Maria De Abreu E Moura -- Corporate social responsibility and financial performance: GIC's share prices value impact - event study / Lucely Vargas -- Corporate social responsibility and cause-related marketing in school sports events: assessing consumption decisions of external stakeholders / Ana Ramos, Helena Alves, Joa<U+0303>o Leita<U+0303>o -- Conceptualization of social entrepreneurship: narratives on avant garde social entrepreneurs from India / Roopinder Oberoi -- Types of corporate social responsibility practices across the industry in Pakistan and their effectiveness / Sania Batool, Aroosha Butt, Beenish Niazi.
Includes bibliographical references.
Print version record
Keywords: Business & Economics -- Development -- Business Development; Business & Economics -- Business Ethics; Corporate governance & responsibilities; Business & management; Social responsibility of business